2015
DOI: 10.1155/2015/460918
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Papillomacular Nerve Fiber Bundle Thickness with Central Visual Function in Open-Angle Glaucoma

Abstract: Purpose. To determine the correlation of reduced retinal thickness in the central papillomacular bundle (CPB) to central visual function, including central retinal sensitivity and visual acuity, in glaucoma patients. Methods. This study enrolled 50 eyes of 50 patients with open-angle glaucoma who were carefully screened for comorbid conditions that can cause decreased central visual function, such as cataracts or macular diseases. We used a novel CPB analysis comprising a program for optical coherence tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
3
11
0
1
Order By: Relevance
“…Similar topical correlations were found in eyes affected by non‐arteritic anterior ischaemic optic neuropathy or glaucoma (Kobayashi et al. ; Rebolleda et al. ).…”
Section: Discussionsupporting
confidence: 75%
“…Similar topical correlations were found in eyes affected by non‐arteritic anterior ischaemic optic neuropathy or glaucoma (Kobayashi et al. ; Rebolleda et al. ).…”
Section: Discussionsupporting
confidence: 75%
“…76 We found that ganglion cell complex thickness in the papillomacular bundle was significantly associated with central visual function, as measured by best-corrected visual acuity and the central 4 measurement points of the Humphrey field analyzer. 77 We also found that blood flow on the temporal side of the ONH was highly associated with ganglion cell complex thickness. 7 These findings suggest that temporal blood flow changes may cause macular function to become more susceptible to damage in patients with glaucoma.…”
Section: Macular Function and Obf In Glaucomasupporting
confidence: 52%
“…Only 19 eyes in our study, however, were diagnosed with severe glaucoma. Other authors like Kobayashi et al [27] demonstrated that RNFL and GCC thickness in the central papillomacular bundle were both strongly correlated with logMAR BCVA ( r value ∼ 0.7, p < 0.01), obtaining a better correlation than BCVA with RNFL and GCC thickness in the macular area.…”
Section: Discussionmentioning
confidence: 84%
“…This suggests that the inferior macula (superior VF) is more susceptible to glaucoma damage than the superior macular region [28] , and regional structural assessment of macular inner retinal layers is a better indicator of central vision than cpRNFL [13,29] . Kobayashi et al [27] also demonstrated that GCC thickness was significantly correlated with VF mean deviation ( r = 0.62, p < 0.01) and with the central 4 thresholds ( r = 0.75, p < 0.01) in patients with open-angle glaucoma, but they used a Humphrey 30-2 (instead of 24-2) pattern to evaluate the macular GCC with a different OCT device (instead of GCIPL thickness). Kim et al [13] revealed, for advanced glaucoma ( n = 86), a stronger relationship between macular VF sensitivity (assessed by calculating the average of sensitivities at 12 central VF points, using a Humphrey 30-2 perimeter) and GCIPL thickness than cpRNFL thickness (particularly temporal cpRNFL thick- ness), and the strongest association between average GCIPL thickness and macular VF sensitivity.…”
Section: Discussionmentioning
confidence: 99%